Deep learning based masked face recognition in the era of the COVID-19 pandemic - Ashwan A. Abdulmunem; Noor D. Al-Shakarchy; Mais Saad Safoq (International Journal of Electrical and Computer Engineering (IJECE), 2023)
During the coronavirus disease 2019 (COVID-19) pandemic, monitoring for wearing masks obtains a crucial attention due to the effect of wearing masks to prevent the spread of coronavirus. This work introduces two deep learning models, the former based on pre-trained convolutional neural network (CNN) which called MobileNetv2, and the latter is a new CNN architecture. These two models have been used to detect masked face with three classes (correct, not correct, and no mask). The experiments conducted on benchmark dataset which is face mask detection dataset from Kaggle. Moreover, the comparison between two models is driven to evaluate the results of these two proposed models.